Planning and Development Strategy of Productive Villages in Pariwari District, Fakfak Regency: (Empirical Review of Community Collegial Factors) - Mohammad Imran Rengen; Sundjoto Sundjoto; Sri Rahayu; Titis Istiqomah (RTTM, 2023)
One of the main tasks of the Government through the sub-district is to provide guidance to the village (kampung). The goal to be achieved in village planning and development is to create a productive community so that it is able to empower and realize its own welfare. The research aims to develop an implementation strategy to arouse the enthusiasm and independence of the village community so that it grows to be productive, so that it can accelerate economic development in Fakfak district. The research was carried out during September – October 2023. Descriptive research method with a combination of quantitative and qualitative analysis approaches. Data was obtained through a direct survey of respondents who had been deliberately determined. The data obtained are given a weight value based on the assessment indicators obtained from the results of the preliminary research. The validity and reliability of the data were tested gradually and in a structured manner using the triangulation and role sharing approaches. The results of the study are presented in the form of a spider web diagram equipped with an illustration of the shift share gap value, and a regression equation model obtained from the SPSS statistical device version 2.3.